Analisis penerapan akuntansi lingkungan pada RSUD DR. Sam Ratulangi Tondano - Sela, Arther Y.; Karamoy, Herman; Mawikere, Lidia M. (Universitas Sam Ratulangi, 2019)
Environmental accounting is an accounting science that shows the real costs of business inputs and processes and ensures cost efficiency, while also being used to measure quality and service costs. The main objective is to comply with environmental protection laws to find efficiencies that reduce environmental impacts. Environmental accounting basically requires the full awareness of other companies or organizations that benefit from the environment. This research was conducted at the hospital, because in hospitals it can produce a lot of waste, therefore hospitals need guidelines to manage waste properly and efficiently with environmental accounting. The purpose of this study is to find out whether the RSUD DR. Sam Ratulangi Tondano has implemented environmental accounting and carried out identification, measurement, recognition, presentation, and disclosure.